Systematic Risk and the Firm's Experimental Strategy - Harpaz, Giora; Thomadakis, Stavros B. (Journal of Financial and Quantitative Analysis, 1982)
The valuation of the firm in the context of the Capital Asset Pricing Model (CAPM) of Sharpe [22] and Lintner [18] brings into a new focus the product ion-investment decisions of the firm faced with demand and cost uncertainty. The market value of the firm and the level of systematic risk which arise from its product ion-investment decisions become items of primary importance. Although there are earlier treatments of the real determinants of valuation and risk in a dynamic context (e.g., Thomadakis [24] and Myers and Turnbull [20]), the case of a firm which experiments for the acquisition of information can furnish new insights.